Metode Pembelajaran Al-Ashwat - Nuril Mufidah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2018)
In Arabic learning, al-Ashwat plays an essential role because al-Ashwat or phonetic is a crucial element in every language. If al-Ashwat is not well understood, Arabic proficiency cannot be mastered perfectly. Often there will be a lack of understanding in the language process. So that the communication process will also be hampered. Learning methods are a way or means to present subject matter. With learning, the approach can simplify and accelerate the learning process towards understanding. There are at least two learning methods that pay attention to the teaching of sound language, including Phonetic Method and Mim-mem Method which is better known as an Audio-Lingual Method.